Evaluation of an integrative Bayesian peptide detection approach on a combinatorial peptide library - Hruska, Miroslav; Holub, Dusan (European journal of mass spectrometry (Chichester, England), 2021)
Detection of peptides lies at the core of bottom-up proteomics analyses. We examined a Bayesian approach to peptide detection, integrating match-based models (fragments, retention time, isotopic distribution, and precursor mass) and peptide prior probability models under a unified probabilistic framework. To assess the relevance of these models and their various combinations, we employed a complete- and a tail-complete search of a low-precursor-mass synthetic peptide library based on oncogenic KRAS peptides. The fragment match was by far the most informative match-based model, while the retention time match was the only remaining such model with an appreciable impact--increasing correct detections by around 8 %. A peptide prior probability model built from a reference proteome greatly improved the detection over a uniform prior, essentially transforming de novo sequencing into a reference-guided search. The knowledge of a correct sequence tag in advance to peptide-spectrum matching had only a moderate impact on peptide detection unless the tag was long and of high certainty. The approach also derived more precise error rates on the analyzed combinatorial peptide library than those estimated using PeptideProphet and Percolator, showing its potential applicability for the detection of homologous peptides. Although the approach requires further computational developments for routine data analysis, it illustrates the value of peptide prior probabilities and presents a Bayesian approach for their incorporation into peptide detection.
Keywords: proteom; Algorithms; Proteomics; prior probability; databáze proteinů; peptide detection; combinatorial peptide library; proteomika; peptidová knihovna; peptidy; Peptides; Databases, Protein; algoritmy; Bayesova věta; Proteome; Peptide Library; Tandem mass spectrometry; Bayes’ theorem; Bayes Theorem